Constant modulus shaped beam synthesis via linear fractional semidefinite relaxation. Issue 11 (11th August 2022) - Dou, Xiuquan; Hu, Mengkai; Liu, Qifan
Abstract: Excitation amplitude control is a critical issue regarding the shaped beam synthesis of array antennas. Ideally, excitations can have the same amplitude, and the desired beam can be achieved only by changing the phases. This method is called constant modulus synthesis, which can reduce the complexity of array antennas and is more conducive to the feeding, but it is really difficult to realize. In this paper, the authors derive a novel constant modulus beam synthesis algorithm, which uses the linear fractional semidefinite relaxation to relax the constant modulus constraints. Simulation results show that this method is stable and can maintain the excitation modulus while realizing the shaped beam.